Photoacoustic section imaging with integrating detectors - Paltauf, G.; Nuster, R.; Gratt, S. (ALT Proceedings, 2026)
Photoacoustic section imaging is a method for visualizing structures with optical contrast in selected layers of an extended object. In order to avoid resolution limitations that are due to commonly used ultrasound detectors of finite size, we propose the use of extended, integrating cylindrical elements for focusing the acoustic detection into the selected section. Two imaging methods based on piezoelectric and optical detection are presented. Resolution limits and results on zebra fish are demonstrated.